Political crises and tourism in Sub-Saharan Africa: destination recovery post-coup d'état. (17th April 2021) - Musavengane, Regis; Zhou, Zibanai
Most African countries are associated with unending political disputes. Instead of amicably ending them, smart power-play approaches continue to degenerate the African nations. The paper therefore seeks to establish the nexus between political crises, coups d'état and tourism in the Sub-Saharan African region and determine destination survival strategies for tourism businesses in environments with a political crisis. Document analysis was adopted to obtain data, this was thematically analysed. The key finding is that military coups are detrimental to tourism. They retard tourism growth by eroding the strides and gains painstakingly made over time through the building of international goodwill. Anholt's hexagon on nation branding is used to suggest strategies that politically disturbed nations can adopt to rejuvenate their tourist destinations.